A Potential and Characteristics Identification of Nanoemulsions Production from CPO using Sonication Methode - Setyowati, Sekar Ayu (2477 - 6165, 2024)
Emulsions are colloidal dispersions of liquids/phases/droplets that do not mix with other liquids, which generally consist of an oil phase and an aqueous phase. Based on the dispersed phase particle size, stability, and appearance emulsions are divided into three categories: conventional emulsions, microemulsions, and nanoemulsions. Sonication is one of the most widely developed methods as it is proven to be more effective in producing nano-sized particles when compared to conventional methods. This research is a preliminary research to determine the best formulation for the preparation of emulsion from CPO using sonication method and to determine the characteristics of CPO emulsion as well as to develop the potential usefulness and economic value of CPO. The variations were 1, 3, 5, 7, 9% (v/v) CPO with distilled water and 5 ml of tween 80 as surfactant. The smallest particle size was obtained in the variation with the amount of CPO 1 ml, which was 188.4 nm and the PDI (Polydispersity Index) value was 0.663, indicating that the particles produced were heterogeneous. Thus, the emulsion produced had a pH between 4-5, a viscosity of about 1 cp, and had good stability during the 14 days of observation.